The Effectiveness of Development of Primary Care Network of Muang Pathum Thani - สุนทรานุรักษ์ ธัญญพัทธ์ (Journal of Preventive Medicine Association of Thailand, 2018)
This research was a cross sectional research. The objectives were to evaluate the ualitative results of effectiveness of development of primary care network at Muang Pathum Thani and satisfaction of patients who received service at Muang Pathum Thani primary care units (PCU), to evaluate the quantitative results, to compare the number of health care staffs before and after health care system development, to compare knowledge of chronically illness care of Village Health Volunteers (VHV) before and after the development, to study patients moved from Pathum Thani Hospital to be treated at PCU, to evaluate an economic effect of primary care development at Muang Pathum Thani. The study populations included health care staff working in the PCU network, VHV, and patients at 11 PCU of Muang Pathum Thani during August 2014 to December 2014. In this study, the number of health care staffs at the PCU and knowledge of VHV in chronically illness care before and after the development were assessed, 538 patients who received service at PCU were interviewed. An economic effects caused by moving service from the Pathum Thani Hospital to the PCU were evaluated. The results were presented in descriptive statistics and compared with paired t-test. The assessment esult showed that the number of health care staffs, who work at the PCU after development of primary care was more than before the development of primary care statistically significant (P<0.001). Knowledge of VHV in caring of chronically patients at home after the workshop were also more than before the workshop statistically significant (P<0.001). The study results of 538 patients who received the service at PCU showed that 46.28% of patients at PCU moved from Pathum Thani Hospital. The satisfaction survey of patients who received the service at PCU showed that 99.81 percent were satisfied. An economic evaluation show that patient who moved to receive service at 11 PCU could reduce cost of transportation and food 17,761.80 baht per month.